Interactions between silica-filled epoxidized natural rubber and fumaric acid / Rohani Abu Bakar @ Nasir - Rohani , Abu Bakar @ Nasir (2016)
Vulcanization is a chemical process that forms crosslinks between the rubber and increases the elasticity and tensile strength of the rubber. The physical properties of the rubber vulcanizates could be further improved through the incorporation of filler, which at the same time reduce the cost of rubber products. Crosslinking of rubber using non-toxic fumaric acid and silica filler could offer a wide range of potential applications. In this work, interactions between silica-filled epoxidized natural rubber (ENR) and fumaric acid were investigated. The silica was isolated from rice husk. Amorphous silica could be produced by combustion of the rice husk and the results from X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) analyses have shown a purity of ~95 %. Purer amorphous silica could be achieved by first leaching the rice husk with dilute acid before combustion. Thus amorphous silica with purity above 99 % was produced after leaching of the rice husk with dilute sulfuric acid prior to combustion at 600 °C for 2 h. ENR with 50 mol % epoxidation (ENR50) containing various loadings of silica was cured with low levels of fumaric acid at 160 °C. Crosslinking reactions of ENR50 with fumaric acid were first studied by Monsanto rheometer, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), differential scanning calorimetry (DSC) and solvent swelling in toluene. The reactions led to the formation of ester linkages and the disappearance of epoxide peak as revealed by FTIR. Incorporation of silica at various loadings in the compound increased the rheometer torque due to the stiffening effect of filler, but there was no observable change in the glass transition temperature (Tg). For physical properties, the tensile strength of the samples slightly increased in spite of the decrease in elongation at break with increasing silica loading. As expected, the modulus at 100 % strain and hardness increased with addition of more filler due to the reduction in relative amount of rubber, resulting in more rigid samples. Upon ageing at 100 °C for 7 days, the tensile strength and elongation at break remained unchanged, but the modulus at 100 % strain slightly increased. On the other hand, sulfur-cured ENR50 containing 30 phr silica exhibited higher tensile strength and elongation at break and further addition of silica weakened these properties. After ageing, the tensile strength reduced by 5 to 7 MPa, whilst elongation at break and modulus at 100 % strain drastically decreased. This study has revealed that fumaric acid could effectively cure ENR to attain comparable physical properties of sulfur-cured ENR.